Blockchain Technology for Winning Consumer Loyalty: Social Norm Analysis Using Structural Equation Modeling - Pérez-Sánchez, María de los Ángeles; Tian, Zhuowei; Barrientos-Baez, Almudena; Gómez-Galán, José; Li, Hanliang (Mathematics, 2021)
Remarkable changes have taken in social operation mode and consumers’ behavior mode because of the foot ban during the pandemic spread of COVID-19. Digital technologies such as Blockchain have shown potential in gaining competitive advantages for enterprises in such situations. This study aims to provide an insight into how to gain consumer loyalty through the use of modern and efficient Blockchain technology. In contrast to the current literature, this study combined the technology acceptance model of planned behavior theory, social exchange theory to explain the loyalty of an online travel agency (OTA) consumer. A self-administered questionnaire was used to collect data from citizens in Hangzhou, a city full of technological innovation atmosphere. Using structural equation modeling with SmartPLS©, responses from 1403 citizens were analyzed. Social norm was discovered to have a positive and significant association with the consumers’ attitude toward technology and thus enhancing the perceived usability and hedonism of OTA application, which can increase consumer loyalty. The findings suggested OTAs may gain consumers’ loyalty through adopting Blockchain technology, and local governments have played a key role in creating such an environment. New technologies have become essential professional and social tools for society. The technological environment and Blockchain within the tourism sector are fundamental elements of China’s economic engine.
Keywords: Blockchain; models; structural equation modeling; social norm; communication; COVID-19; Chinese tourism; loyalty; Scopus; WOS(2)